EVALUASI KELAYAKAN STRUKTUR JEMBATAN GELAGAR KOMPOSIT BENTANG 40 M BERDASARKAN NILAI SISA KAPASITAS JEMBATAN Studi Kasus Jembatan Kuranji, Provinsi Sumatera Barat - , AZWAR ANAS; , Akhmad Aminullah, S.T., M.T., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bridge is a structure built to provide transportation routes over river, valley or the sea. The bridge can be facilitate interaction people from region one to the others. In order to give safety and comfortable bridge, it must be always evaluate to know its existing condition. In this final project, proper capacity for superstructure bridge have been evaluated remaining capacity for Kuranji Bridge that located in Sumatera Barat Province. Kuranji bridge is composite steel plate girder with 120 m total length and 40 m length of each span. This final project used field data survey that collect quality of concrete data and dimensions data. Loading standard refers to RSNI T-02-2005, analysis of structure capacity refers to RSNI T-03-2005 and remaining capacity analysis used rating factor analysis in operating condition and inventory condition that refers to Pedoman Penentuan Nilai Sisa Kapasitas Jembatan 024/BM/2011. For comparison, analysis of structure using Pedoman Perencanaan Pembebanan Jembatan Jalan Raya (PPPJJR) 1987. The analysis result with rating factor analysis is Kuranji bridge superstructure incapable of supporting traffic âDâ load. However, bridge superstructure still capable of supporting truck load in operating condition with critical rating factor that 1,116 (for moment) and 3,685 (for shear). Analysis refers to Pedoman Pembebanan Jembatan Jalan Raya (PPPJJR) 1987, bridge superstructure still capable to supported because the analysis design concept used ASD (Allowable Stress Design) that used serviceability loads. In order to keep bridge safety operated, it need vehicle loads limited or gave strengthening for the critical elements.